Increasing Hard Winter Wheat Yield Potential via Synthetic Hexaploid Wheat: II. Heritability and Combining Ability of Yield and its Components. Issue 1 (1st January 2013) - Cooper, Jessica K.; Ibrahim, Amir M. H.; Rudd, Jackie; Hays, Dirk; Malla, Subas; Baker, Jason
Abstract : Introgression of new genes through crosses to synthetic hexaploid wheat [ Triticum turgidum L. subsp. durum (Desf.) Husn. (syn. Triticum durum Desf.) × Aegilops tauschii Coss.] could contribute to the improvement of winter wheat ( Triticum aestivum L). The purpose of this research was to explore the heritability of traits and combining ability of synthetic wheat in Texas. Ten elite primary synthetics from the International Maize and Wheat Improvement Center (CIMMYT), screened for desirable traits, were backcrossed to two Texas cultivars, 'TAM 111' and 'TAM 112'. Heritability of traits and combining ability of genotypes for traits related to yield were determined in the BCF4 and BCF5 populations across five Texas locations in 2009 and 2010, respectively. Heritability estimates differed across locations. Single‐seed weight was the most heritable trait whereas yield was the least heritable trait. Primary synthetics that produced progeny superior to TAM 111 or TAM 112 were identified. Synthetics with high combining ability for yield also had high combining ability for head number or seed per head. This study suggests improved yield could result from selecting for increased seed per head in lines derived from synthetic populations.